Differential regulation of lineage commitment in human and mouse primed pluripotent stem cells by the nucleosome remodelling and deacetylation complex - Ramy Ragheb; Sarah Gharbi; Julie Cramard; Oluwaseun Ogundele; Susan L. Kloet; Thomas Burgold; Michiel Vermeulen; Nicola Reynolds; Brian Hendrich (Stem Cell Research, 2020)
Differentiation of mammalian pluripotent cells involves large-scale changes in transcription and, among the molecules that orchestrate these changes, chromatin remodellers are essential to initiate, establish and maintain a new gene regulatory network. The Nucleosome Remodelling and Deacetylation (NuRD) complex is a highly conserved chromatin remodeller which fine-tunes gene expression in embryonic stem cells. While the function of NuRD in mouse pluripotent cells has been well defined, no study yet has defined NuRD function in human pluripotent cells. Here we find that while NuRD activity is required for lineage commitment from primed pluripotency in both human and mouse cells, the nature of this requirement is surprisingly different. While mouse embryonic stem cells (mESC) and epiblast stem cells (mEpiSC) require NuRD to maintain an appropriate differentiation trajectory as judged by gene expression profiling, human induced pluripotent stem cells (hiPSC) lacking NuRD fail to even initiate these trajectories. Further, while NuRD activity is dispensable for self-renewal of mESCs and mEpiSCs, hiPSCs require NuRD to maintain a stable self-renewing state. These studies reveal that failure to properly fine-tune gene expression and/or to reduce transcriptional noise through the action of a highly conserved chromatin remodeller can have different consequences in human and mouse pluripotent stem cells.